The specificity of binding of growth hormone and prolactin to purified plasma membranes from pregnant-rabbit liver. - Webb, C F (1986)
The binding of 125I-labelled human growth hormone (hGH) to a purified plasma membrane preparation from the liver of pregnant rabbit, and to receptors solubilized from this fraction with Triton X-100, was dependent on time, temperature, the cations used and the receptor concentration. Solubilization did not affect the binding properties of the receptors at low concentrations of Triton X-100. Some somatogenic hormones, such as bovine GH, and some lactogenic hormones, such as ovine prolactin, displaced 125I-labelled hGH from purified plasma membranes and solubilized receptor preparations, but GHs and prolactins from various other species were rather ineffective. The results indicate that although there are binding sites for hGH in these pregnant rabbit liver membranes, few of these are specifically somatogenic or lactogenic. The binding properties of the purified plasma membranes are similar to those of a microsomal preparation studied previously, suggesting that the complex nature of the binding of hGH is not due to the heterogeneity of cellular membranes used to study binding, but is a property of the receptors associated with plasma membranes.